Improvement of the Budget Forecasting System in the Kyrgyz Republic - AMANBAEVA, Chynara; AKYLBEKOVA, Nelli; ZAITENOVA, Nazym; BAITOKOVA, Makhabat; OMUROVA, Saltanat (Theoretical and Practical Research in Economic Fields, 2024)
The purpose of this study is to develop and propose measures to improve the budget forecasting system in Central Asia to enhance the accuracy, reliability, and adaptability of budget forecasts. The study involved a comprehensive analysis of data covering various aspects of budget forecasting in Central Asian countries. This analysis included the collection of extensive data, including statistical indicators, on budget forecasts, and factors influencing economic stability in the region. The research results underscored the importance of budget forecasting as a tool for strategic financial planning based on systemic analysis and the use of advanced technologies. The concept of budget forecasting was highlighted as a systematic analysis aimed at predicting the financial performance of an organization over a specific period, including assessing expected income and expenses considering various factors influencing the financial situation. The study also examined the key functions of budget forecasting, including financial resource planning, optimization, and financial stability control. Special attention was paid to analysing the impact of external factors, such as economic uncertainty, using statistical methods and scenario analysis. The study also emphasized the importance of modern technologies, including machine learning and big data analysis, in improving budget forecasting processes. Overall, the research findings present important insights for practical application and further research in the field of financial management and budget planning. The findings have the potential to be used in shaping policies and reforms aimed at sustainable development and efficient utilization of public finances in the region.